Analysis of selected heavy metals in Malaysian foundation cosmetics using Atomic Absorption Spectrophotometry (AAS) - Muhamad Ezzas, Nur Izzdiana; Mahidi, Muhammad Haiqal; Muhamad Sahapini, Noor Fadhilah; Mohamed, Siti Mazleena (2024)
Beauty products are widely used to enhance appearance, but many contain harmful heavy metals. This study analyzed Cu, Cd, Cr, Mn, Ni, and Zn levels in five popular Malaysian foundation brands—Bihan, CPG, Cubremi, Kamelia, and Maaez—using flame atomic absorption spectrophotometry. The metals were detected in all samples, with concentrations ranging from 0.018 ppm to 1.012 ppm. Maaez had the highest copper and zinc levels, Bihan had the highest cadmium and manganese, and Cubremi had elevated nickel. Despite varying concentrations, none of the samples exceeded the WHO’s permissible limits for heavy metals in cosmetics.